IMPROVEMENT IN BOWEL URGENCY IS ASSOCIATED WITH STOOL FREQUENCY AND RECTAL BLEEDING REMISSION AT 12 AND 52 WEEKS IN PATIENTS WITH MODERATELY-TO-SEVERELY ACTIVE ULCERATIVE COLITIS. (26th January 2023) - Long, Millie; Gisbert, Javier; McGinnis, Kim; Ferrante, Marc; Rogler, Gerhard; Sapin, Christophe; Hunter, Theresa; Milata, Joe; Navabi, Seyedehsan
Abstract: INTRODUCTION: Mirikizumab, an anti-IL23p19 antibody, has demonstrated safety and efficacy versus placebo across clinical remission, symptomatic remission, and endoscopic and histologic endpoints in patients with moderately-to-severely active ulcerative colitis (UC) in a Phase 3, double-blind, 12-week induction study (LUCENT-1/NCT03518086) and 40-week maintenance study (LUCENT-2/NCT03524092). Here, we examine the relationship between bowel urgency (BU) clinically meaningful improvement (CMI) and BU remission with rectal bleeding (RB) remission and stool frequency (SF) remission (Table 1 for definitions). METHODS: Patients in LUCENT-1 (N=1281) were randomly assigned 3:1 to receive intravenous mirikizumab 300mg or placebo every four weeks (Q4W) for a total of 12 weeks. Patients who achieved clinical response to mirikizumab by Week 12 of LUCENT-1 (N=544) were re-randomized 2:1 to subcutaneous mirikizumab 200mg or placebo Q4W for 40 weeks in LUCENT-2 (maintenance study). Patients recorded their BU severity in the previous 24 hours using an 11-point Urgency Numeric Rating Scale (UNRS; 0=no urgency to 10=worst possible urgency) in an electronic daily diary. Weekly scores were averaged for patients with at least 4 of 7 days of complete diary data. BU remission was defined as UNRS score of 0 or 1, and BU CMI was defined as ≥3-point decrease in UNRS score compared to baseline. For patients who achieved clinical response at the end of induction, analyses were repeated for the end of maintenance at Week 40 (for 52 weeks of continuous treatment). Patients with UNRS<3 at baseline were not included in this analysis. RESULTS: A total of 1087 patients reported a baseline UNRS score ≥3. Patients achieving BU CMI had significantly higher rates of RB remission and SF remission at both Week 12 and Week 40 compared with patients not achieving these outcomes (all p<0.001, Table 1, Figure 1). Similarly, at Week 12 and Week 40, patients achieving BU remission had significantly higher rates of achieving RB remission and SF remission compared to those who did not achieve BU remission (all p<0.001, Table 1, Figure 1). CONCLUSION: A higher proportion of patients enrolled in LUCENT-1 and -2 who achieved BU CMI and BU remission achieved RB remission and SF remission. These results support that the symptom of bowel urgency is an important marker of UC disease activity that is related to and distinct from other commonly accepted symptoms of active UC.